2007
DOI: 10.1562/0031-8655(2000)0710700teospe2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Suntan Parlor Exposure on Delayed and Contact Hypersensitivity

Abstract: Cutaneous and systemic immune function are believed to play an important role in cutaneous carcinogenesis. We therefore sought to determine whether the suntan parlor radiation sources commonly used in the United States cause measurable qualitative suppression of immune function and quantitative alterations in circulating T cell subpopulations. Subjects (n = 22) were recruited and randomly assigned to receive suntan parlor exposures (10 full‐body UV exposures over a 2 week period, shielding only the right flexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Because of ethical and other difficulties in selecting a suitable hapten, few studies have assessed the effect of repeated UVR on the generation of CHS. Whitmore and Morison (52) irradiated volunteers with 10 whole-body UV exposures (95% UVA, 5% UVB) over 2 weeks, starting at 0.7 MED and increasing on each occasion, although remaining suberythemal throughout. The sensitizer, dinitrochlorobenzene (DNCB), was applied to an irradiated site immediately following the final UVR.…”
Section: Contact Hypersensitivitymentioning
confidence: 99%
“…Because of ethical and other difficulties in selecting a suitable hapten, few studies have assessed the effect of repeated UVR on the generation of CHS. Whitmore and Morison (52) irradiated volunteers with 10 whole-body UV exposures (95% UVA, 5% UVB) over 2 weeks, starting at 0.7 MED and increasing on each occasion, although remaining suberythemal throughout. The sensitizer, dinitrochlorobenzene (DNCB), was applied to an irradiated site immediately following the final UVR.…”
Section: Contact Hypersensitivitymentioning
confidence: 99%
“…More recently, Whitmore and Morison (2000) reported that 10 full-body exposures over a two-week period suppressed immunity as assessed by the induction and elicitation arms of the contact hypersensitivity response (CHS). These authors also studied the effect of 10 full-body tanning exposures in 11 volunteers and, not surprisingly, reported the presence of CPD and p53 protein expression in keratinocytes in vivo (Whitmore et al, 2001).…”
Section: Acute and Non Skin Cancer Effectsmentioning
confidence: 99%